Bioactive Secondary Metabolites from Phomopsis sp., an Endophytic Fungus from Senna spectabilis - Chapla, Vanessa Mara [UNESP]; Zeraik, Maria Luiza [UNESP]; Ximenes, Valdecir F. [UNESP]; Zanardi, Lisineia Maria [UNESP]; Lopes, Márcia Nasser [UNESP]; Cavalheiro, Alberto José [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Young, Maria Claudia M.; Fonseca, Luiz Marcos da [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Araújo, Angela Regina [UNESP] (Mdpi Ag, 2014)
Chemical investigation of an acetonitrile fraction from the endophytic fungus Phomopsis sp. led to the isolation of the new natural product 2-hydroxy-alternariol (7) together with the known compounds cytochalasins J (1) and H (2), 5'-epialtenuene (3) and the mycotoxins alternariol monomethyl ether (AME, 4), alternariol (AOH, 5) and cytosporone C (6). The structure of the new compound was elucidated by using 1-D and 2-D NMR (nuclear magnetic resonance) and high resolution mass spectrometry. The cytochalasins J (1) and H (2) and AOH (5) exhibited potent inhibition of the total ROS (reactive oxygen species) produced by stimulated human neutrophils and acted as potent potential anti-inflammatory agents. Moreover, cytochalasin H (2) demonstrated antifungal and acetylcholinesterase enzyme (AChE) inhibition in vitro.
Keywords: secondary metabolites; bioactivities; endophytic fungi; Phomopsis sp.; Senna spectabilis